EDUCATION OF TOLERANCE IN SCHOOLCHILDREN IN THE CONTEXT OF A POLYCULTURAL SOCIETY - Svitlana Dovbenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Polycultural education is considered as a process of creating conditions for schoolchildren to develop a worldview setting for constructive cooperation by engaging in ethnic, native and world cultures, developing planetary consciousness on this basis, forming readiness and ability to live in a multinational society. The process of education of tolerance in schoolchildren a multicultural educational environment is considered in three aspects: acquiring a particular philosophy of tolerance as a value; culture of tolerant consciousness; attitude to the appropriate reality that is embodied in real behaviour. The conditions for the efficiency of education of tolerance in schoolchildren in the context of a multicultural society are: multicultural content of the educational process; organization of a tolerant environment that ensures tolerant interaction between the subjects of the educational process; the use of interactive, personality-oriented, reflexive and dialogic technologies, which are aimed to develop the tolerant qualities of schoolchildren; developed tolerant qualities of the teacher's personality and his/her competence in the issue of education of tolerance.